2018
DOI: 10.1002/dev.21601
|View full text |Cite
|
Sign up to set email alerts
|

Low childhood subjective social status and telomere length in adulthood: The role of attachment orientations

Abstract: Low subjective social status (SSS) in childhood places one at greater risk of a number of health problems in adulthood. Theoretical and empirical evidence indicates that exposure to supportive parenting may buffer the negative effects of low childhood SSS on adult health. Given the importance of supportive caregivers and close others for the development of attachment orientations throughout the lifespan, attachment theory may be important for understanding why some individuals are resilient to the negative eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Previous literature, however, shows that telomere length is impacted by several different factors (e.g., physical activity and gender) (Arsenis et al, 2017;Starkweather et al, 2014). Although these associations were not present in the current sample, other telomere length-related studies control for these factors; accordingly, we controlled for these factors to maintain consistency across studies (e.g., Murdock et al, 2018).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Previous literature, however, shows that telomere length is impacted by several different factors (e.g., physical activity and gender) (Arsenis et al, 2017;Starkweather et al, 2014). Although these associations were not present in the current sample, other telomere length-related studies control for these factors; accordingly, we controlled for these factors to maintain consistency across studies (e.g., Murdock et al, 2018).…”
Section: Discussionmentioning
confidence: 71%
“…All samples were run in duplicate (Cohen et al, 2016). Replicate values were averaged to determine a final T:S ratio (Murdock et al, 2018). Higher T:S ratios signify longer telomere length (Kroenke et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this theory, research has shown that genetic factors, epigenetic processes, personality traits (e.g., neuroticism), and social environmental conditions during childhood and adolescence (e.g., social/financial stress, uncertainty, abuse, or neglect) play a role in shaping individuals' sensitivity to lateroccurring adverse life events (25,36). At the molecular level, epigenetic regulation of gene transcription can play an important role in helping individuals adapt to challenges posed by the external social environmental (37).…”
Section: Social Signal Transduction Theory Of Depressionmentioning
confidence: 93%
“…Specifically, stress exposure during childhood can alter behavioral and physiological responses to acute and chronic stress in adulthood that in turn influence later-life risk for mental and physical health problems, including anxiety disorder, depression, CVD, and autoimmune and neurodegenerative disorders ( 20 , 39 , 47 , 140 , 179 ). Epigenetic changes and immune system dysregulation may be potential pathways that underlie this link ( 36 , 39 , 180 ). Indeed, the presence of multiple childhood adversities has been found to heighten emotional and physical reactivity to subsequent stress, which in turn activates genetic and epigenetic processes that may promote a proinflammatory phenotype ( 20 ).…”
Section: Psychobiological Mechanisms Linking Bereavement and Healthmentioning
confidence: 99%